2012
DOI: 10.2134/agronj2012.0014
|View full text |Cite
|
Sign up to set email alerts
|

Maize Evapotranspiration and Water‐Use Efficiency in Response to Row Spacing

Abstract: Reduced row spacing has shown to increase maize (Zea mays L.) yield; however there are conflicting results on whether narrow rows increases maize crop evapotranspiration and/or water use efficiency. This work analyzes the response of maize yield, crop evapotranspiration (ET) and water use efficiency to reduced row spacing under different water and N regimes. Maize crops were grown at Balcarce, Argentina, during two seasons. Treatments included two water regimes (rain‐fed and irrigated), two rows spacing (35 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Second, the soil water content at sowing was generally greater in the T3 treatment than in the T2 treatment (Fig. 2) due to film mulching for the non‐growth season, and the ET was positively correlated with the soil water supply during the growth season (Barbieri et al, 2012; Zhang et al, 2013). This soil water content difference could also explain why the ET of each treatment in 2012 was higher than that in 2010 and 2011 and why the ET of the T4 treatment was higher than that in the other three treatments in 2011 (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the soil water content at sowing was generally greater in the T3 treatment than in the T2 treatment (Fig. 2) due to film mulching for the non‐growth season, and the ET was positively correlated with the soil water supply during the growth season (Barbieri et al, 2012; Zhang et al, 2013). This soil water content difference could also explain why the ET of each treatment in 2012 was higher than that in 2010 and 2011 and why the ET of the T4 treatment was higher than that in the other three treatments in 2011 (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, WUE was lower in treatments with wider row spacing. Barbieri et al (2012) found a higher yield of maize when reducing row spacing from 70 to 35 cm. Narrower rows increased early season evapotranspiration and overall water-use efficiency.…”
Section: Reduced Stand Densitymentioning
confidence: 91%
“…As well, at Swift Current, evapotranspiration by pulses and spring wheat are independent of stubble height (Cutforth and McConkey, 1997;Cutforth et al, 2002Cutforth et al, , 2011. In addition, others have found row spacing had a limited effect on crop water uptake (Chen et al, 2010;Barbieri et al, 2012). No significant interactions of row spacing and stubble height on WU were observed.…”
Section: Locationmentioning
confidence: 91%